Environmental and ecotoxicological effects of drugs used for the treatment of COVID 19 - Efrain Merma Chacca, Donal; Maldonado, Ingrid; Vilca, Franz Zirena (Frontiers in Environmental Science, 2022)
Consumption of different pharmaceutical products has been increasing since the COVID-19 pandemic. Some health institutions worldwide approved using drugs such as ivermectin, hydroxychloroquine, and azithromycin for the virus treatment. Once consumed by humans, these compounds are released in urine and faeces, ending in wastewater and conducted to treatment plants or directly discharged without prior treatment into surface waters and soil, with minimum values recorded between 7 ng/L and <0.08 μg/L for azithromycin and ivermectin respectively. Their presence has numerous toxicological effects on aquatic and terrestrial species, influencing population decline and altering the growth of organisms. However, the environmental consequences of the presence of pharmaceuticals in the environment are poorly understood. This work aims to analyze information on the presence of three drugs, ivermectin, azithromycin, and hydroxychloroquine, focusing on aquatic and terrestrial ecosystems since this is where it arrives through wastewater. Ecotoxicological effects on flora, fauna and humans are also analyzed. Once there, they persist in the environment causing severe ecological damage, development and growth disorders in animals and plants, and in many cases, even the death of species.